Teologi Asy'ariyah dan Klaim Pembelaannya Terhadap Mazhab Salaf - Muhammad Istiqamah; Syandri, Syandri (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
This study aims to explain the opinions of Asy'ariyah theology and its comparison with the salaf mazhab. This research is qualitative descriptive research with library research techniques that use normative theological approaches. The results of this study show that Asy'ariyah in various discussions of the creed has its own opinions of Islamic creed, ranging from the first obligation of a mukallaf, the meaning of tawhid, al-imÄn, asmÄ' wa á¹£ifat, kalam Allah, rukyatullÄh, to qaá¸Ä' and qadar. Even in one matter, among the Assyrians had different views. As for the comparative study between Asy'ariyah theology and salaf mazhab found a considerable difference between the two. Both in the matter of the first obligation as a mukallaf, regarding kalamullah, the attributes of Allah, destiny, or the matter of faith, so that the defense of the salaf mazhab echoed by Asy'ariyah is only an unproven claim.